Design and Application of Daylight-Based Lighting Controller on LED Luminaire - Sulee Bunjongjit; Santipont Ananwattanaporn; Atthapol Ngaopitakkul; Chaiyan Jettanasen; Theerasak Patcharoen (My University, 2020)
This paper proposes a control circuit for Light Emitting Diode (LED) luminaire based on the amount of daylight. This system uses both natural daylight and artificial light from a luminaire to reach the desired illuminance on a working plane. The control circuit operates by receiving an illuminance value from a light sensor and comparing it with a set value in the microcontroller before limiting the light intensity of LED by sending a control Pulse Width Modulation (PWM) signal to the LED driver. In the experimental setup, the controller and a physical model of a working space were built in order to field test the LED daylight control circuit. Electrical characteristics such as voltage, current, and power were measured with a power meter. Illumination characteristics in terms of illuminance on a working plane were determined using a lux meter. The results from actual field tests revealed that this LED control circuit was able to reduce the power consumption of the lighting system while keeping the illuminance on the working plane at the standard value. Both simulation results and the actual experiment of the control circuit proved that it could be used to improve the energy efficiency of both newly installed and retrofitted lighting systems.
Keywords: Daylight; LED lamp; Electric light; Impact of Light on Environment and Health